Resource-Based View of Information Systems: Sustainable and Transient Competitive Advantage Perspectives - Gaurav Gupta (Australasian Journal of Information Systems, 2018)
The resource-based view (RBV), or resource-based theory, is one of the oldest and most influential theories in the field of information systems. This paper contends that it is timely to revisit, reflect on, and reposition RBV to ensure its continued disciplinary relevance and progress. In doing so, this paper (i) provides a succinct and sharp evaluation of the conventional RBV of information systems that firms use to establish sustainable competitive advantage, and (ii) makes an original contribution by introducing a contemporary RBV of information systems that firms can use to establish transient competitive advantage. Both these contributions should advance the current and future understanding of information systems as (a) an internal firm resource, (b) a source of competitive advantage, and (c) a driver of firm performance.